Higher Incidence of Atrial Fibrillation in Left Ventricular-to-Right Atrial Shunt Patients - Chou, Hongda; Chen, Hongxia; Xie, Juan; Xu, Aiqing; Mu, Guanyu; Han, Fei; Tse, Gary; Li, Guangping; Liu, Tong; Fu, Huaying (Frontiers in Physiology, 2020)
Background: A possible association between atrial fibrillation (AF) and left ventricular-to-right atrial shunt (LVRAS) has been reported. The present study investigated the incidence of AF in LVRAS. Methods: This was a retrospective study of consecutive patients undergoing echocardiography at a single tertiary center. Clinical data, laboratory results and echocardiography parameters such as right atrial area (RAA), right ventricular end diastolic diameter (RVDD) and left atrial diameter (LAD) were compared between LVRAS group and non-LVRAS patients, and between AF and non-AF patients. Logistic regression analysis was performed. Propensity score matching was performed between patients with both LVRAS with AF and LVRAS without AF. Results: A total of 3436 patients were included, and the incidence of LVRAS was 1.16% (n=40). The LVRAS group had significantly larger RAA, RVDD and LAD in LVRAS group compared with non-LVRAS group. For the LVRAS group, those who suffered from AF showed larger RAA, RVDD and LAD compared with those who maintained sinus rhythm. Multivariable logistic regression showed that gender (OR: 0.608), age (OR: 1.048), LAD (OR: 1.111), mPAP (OR: 1.023), TR (OR: 2.309) and LVRAS (OR: 12.217) were significant factors for AF. Conclusions: Our study suggested that LVRAS, TR, LAD, mPAP, age and male were risk factors for AF. RA enlargement might underlie mechanism in the higher incidence of AF in LVRAS patients. These findings should be confirmed in larger prospective studies.